Validation of the diagnostic criteria of the consensus definition of fracture-related infection. Issue 6 (June 2022) - Onsea, Jolien; Van Lieshout, Esther M.M.; Zalavras, Charalampos; Sliepen, Jonathan; Depypere, Melissa; Noppe, Nathalie; Ferguson, Jamie; Verhofstad, Michael H.J.; Govaert, Geertje A.M.; IJpma, Frank F.A.; McNally, Martin A.; Metsemakers, Willem-Jan
Highlights: This study validates the confirmatory criteria of the fracture-related infection consensus definition. The presence of at least one confirmatory criterion identifies the vast majority of patients with a fracture-related infection. Infection is highly likely in case of the presence of a single positive culture with a virulent pathogen. Specificities of at least 95% were found for the clinical suggestive signs of fever, wound drainage, local warmth and redness. Abstract: Background: The recently developed fracture-related infection (FRI) consensus definition, which is based on specific diagnostic criteria, has not been fully validated in clinical studies. We aimed to determine the diagnostic performance of the criteria of the FRI consensus definition and evaluated the effect of the combination of certain suggestive and confirmatory criteria on the diagnostic performance. Methods: A multicenter, multi-national, retrospective cohort study was performed. Patients were subdivided into an FRI or a control group, according to the treatment they received and the recommendations from a multidisciplinary team ('intention to treat'). Exclusion criteria were patients with an FRI diagnosed outside the study period, patients younger than 18 years of age, patients with pathological fractures or patients with fractures of the skull, cervical, thoracic and lumbar spine. Minimum follow up for all patients was 18 months. Results: Overall, 637 patients underwent revision surgery for suspicion of FRI. Of these, 480 patients were diagnosed with FRI, treated accordingly, and included in the FRI group. The other 157 patients were included in the control group. The presence of at least one confirmatory sign was associated with a sensitivity of 97.5%, a specificity of 100% and a high discriminatory value (AUROC 0.99, p  < 0.001). The presence of a clinical confirmatory criterion or, if not present, at least one positive culture was associated with the highest diagnostic performance (sensitivity: 98.6%, specificity: 100%, AUROC: 0.99 ( p <  0.001)). In the subgroup of patients without clinical confirmatory signs at presentation, specificities of at least 95% were found for the clinical suggestive signs of fever, wound drainage, local warmth and redness. Conclusions: The presence of at least one confirmatory criterion identifies the vast majority of patients with an FRI and was associated with an excellent diagnostic discriminatory value. Therefore, our study validates the confirmatory criteria of the FRI consensus definition. Infection is highly likely in case of the presence of a single positive culture with a virulent pathogen. When certain clinical suggestive signs (e.g., wound drainage) are observed (individually or in combination and even without a confirmatory criterion), it is more likely than not, that an infection is present.